Екосистеми державного управління у цифровому суспільстві - Горішня, К. О. (ХНУРЕ, 2024)
The article is devoted to issues of development within the information society of latest schemes of regulation of socio-economic processes and creation of an ecosystem of public administration. It is proven that the main condition for the sustainable development of such ecosystems is to increase the efficiency of the state social and economic policy. In order to achieve this goal, the state accumulates information about citizens and organizations, certain groups and integration projects in single digital sources. This process is carried out by those organizational management structures that have the authority to develop new ways of interaction between citizens of private structures and state bodies
Keywords: екосистема